2015
DOI: 10.1039/c5ra15220h
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme activity enhancement of chondroitinase ABC I from Proteus vulgaris by site-directed mutagenesis

Abstract: Arg660 was found as a new active site and Asn795Ala and Trp818Ala mutants showed higher activities than the wild type based on molecular docking simulation analysis for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 42 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…1). It was reported that furfural of 10 mM (approximately 1 g/L) slightly increased Thermoanaerobacter pseudethanolicus ’s cell yield by 11% [35]. Furfural could replace glycerol as an electron sink and allow less carbon loss to byproducts and more carbon distribution towards biomass synthesis [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). It was reported that furfural of 10 mM (approximately 1 g/L) slightly increased Thermoanaerobacter pseudethanolicus ’s cell yield by 11% [35]. Furfural could replace glycerol as an electron sink and allow less carbon loss to byproducts and more carbon distribution towards biomass synthesis [36].…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of furfural was measured by HPLC. The expression of ctADH1 was confirmed by SDS-PAGE analysis [35]. …”
Section: Methodsmentioning
confidence: 99%
“…The tertiary structure of PobA complexed with 4‐HBA and FAD (PDB code: 1IUV) (Gatti et al, ) was downloaded from the Protein Data Bank (http://www.rcsb.org). Substrate of 1IUV model was substituted with 3,4‐DHBA using Discovery Studio (version 2.5) (Chen et al, ). Hydrogen bonds of complexes were analyzed by PyMOL (version 1.7).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, others reported the diverse stability of ChABC vs temperature. 33 In our work, we showed that the activity of wild-type ChABC was higher than in standard conditions (controls) for 7 days at 37°C ( Figure 1B) in sucrose solutions, thus suggesting that exposure of ChABC to sucrose could enhance its thermostability and prolong its activity for days. 19 In particular, after 1 day, the ChABC in Sal lost more than 98% of enzyme activity, confirming the instability of the enzyme at body temperature.…”
Section: Discussionmentioning
confidence: 52%